Development of Interactive Learning Media with Android-Based Simulative Approach on Genetic Substance and Protein Synthesis - Fatmawati, Umi; Yuniar, Rizka; Nurmiyati, Nurmiyati (Bioedusiana: Jurnal Pendidikan Biologi, 2023)
Biology learning is inseparable from observation activities, but not all the concepts apply by observation activities, therefore called abstract concepts. One of the abstract concepts in biology learning is the concept of genetic substance and protein synthesis. Learning abstract concepts needs suitable media to make it easier for students to visualize them. This study aims to develop and perceive the characteristic of interactive learning media with an android-based simulative approach to genetic substance and protein synthesis and determine its feasibility and practicality. This research used a research model adapted from Thiagarajan in a 4D model and modified it into a 3D model (defining, designing, developing). The results of this study are interactive learning media with an android-based simulative approach on the topic of genetic substances and protein synthesis, which consists of several menus namely competencies, materials, learning videos, simulation activities, evaluations, and discussion forums. Assessment of media feasibility based on the assessment of material experts, the score is 77.78% (feasible) and media experts 81.94% (very feasible). The practicality assessment by practitioners is 92.5% (very practical), limited trial results in 83.17% (very practical), and field trial results in 86.34% (very practical). The study results indicate that interactive learning media is feasible and practical to use as learning media.